ANALISIS PERBANDINGAN PENERAPAN TARIF PAJAK TUNGGAL TERHADAP TARIF PAJAK PROGRESSIF ATAS BEBERAPA LAPISAN PENGHASILAN WAJIB PAJAK BADAN DI INDONESIA - Daniel Peterson; Iwan Siswandi (Universitas Bunda Mulia, 2017)
The purpose and intention for this research is about to deliver an information about the implementation and the impact due to single rate tax income in Indonesia. Involving the efficiency and economical advantages for corporation and other business entities.The platform of this research is Analytic Descriptive type and generating secondary data for being analyzed. The main result of this result that due to implementation of single rate income tax affects to earning after tax or net income. The Government assigned this policy to make a well balance tax collection for each layers of business. The conclution is the implementation of single rate tax has a main goal, which is to increase the total revenue from taxation in a long term period by creating a condusive economic environmental to attract more investment in Indonesia.Key Word : Single Rate Tax Income, Progressif Rate Tax Income